Effect Of Nutritional Status On Object Ability Of Children's Object Controls Aged 5 To 6 Years - Lucy Pratama Putri; Septri Septri; Zumroni Zumroni; Oktarifaldi Oktarifaldi; Risky Syahputra; Ibnu Andli Marta; Syahrial Bakthiar; Anggri Dwi Nata (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2020)
Low basic mobility skills in children aged 5 to 6 years in the 2x11 Kayu Tanam sub-district are difficult. Whereas this basic movement skill is the initial foundation in realizing more complex movements in the future, such as physical activity and more specific sports activities. Basic motion skills are divided into two, the ability of object control and locomotor. One aspect that supports basic movement skills is nutritional status. This study aims to determine the effect of nutritional status on the ability of object control children aged 5 to 6 years in 2x11 Kayu Tanam District. The research method used is simple linear regression. The population in this study were children aged 5 to 6 years and samples were taken by random sampling with a total of 83 children. Nutrition status data is obtained through height and weight measurements and the ability of the control object using the TGMD-2 instrument. The results showed that there was an influence of nutritional status on the ability of object control children aged 5 to 5 years in 2x11 Kayu Tanam District with sig 0,000 <?= 0.05 and the effect of 24.3%.